A novel bandwidth enhanced triple band antenna for satellite and airborne applications - Mohammed Ismail Mohammed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents a novel bandwidth enhancement technique in which a passive stack of third order Sierpinski carpet fractal antenna is parasitically coupled to the driven element that is also a Sierpinski fractal of third order. Edge feeding technique is used. The passive stack placed symmetric to the driven elements provide the combined benefits of horizontal and vertical parasitic coupling, with added advantage of miniaturization contributed by fractal technology. Result of the study indicate that the antenna array provide triple band with a large inter-band separation that mitigates the effects of inter-band interference. The first band at 6.1Ghz with bandwidth of 250Mhz supports mobile wireless and fixed satellite service, the second band at 7.1Ghz with 350Mhz bandwidth supports mobile wireless, fixed wireless and fixed satellite service. The third band is at 11.6Ghz with bandwidth of 1.4Ghz and supports fixed wireless and fixed satellite services. The number of elements in the parasitic stack influence array performance in terms of bandwidth, gain and directivity. The bandwidth in the third band increased from 1.5Ghz for two-element stack to 1.7Ghz for three-element. This has an advantage over conventional antenna array, that use more active antenna elements that have the limitations of more power consumption and large space occupancy.